Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Pegawai (Study Pada Pegawai Politeknik Negeri Malang) - Soni Refiansyah; Khalikussabir Khalikussabir; Muhammad Sirojuddin Amin (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of Transformational Leadership Style, Work Motivation, and Job Satisfaction on the Performance of Employees at the State Polytechnic of Malang. This study uses a quantitative approach with a research population of 190 non-ASN employees of the State Polytechnic of Malang. The sampling technique used proportional random sampling and purposive sampling and obtained a sample of 66 employees. Data collection was carried out through questionnaires and analyzed using multiple linear regression to test the influence of independent variables on employee performance. The results of the study indicate that leadership style has a positive and significant effect on employee performance. In addition, work motivation also has a significant positive effect on employee performance and job satisfaction has a positive and significant effect on employee performance at the State Polytechnic of Malang. The results indicate an increase in the effectiveness of transformational leadership and optimal motivation and job satisfaction can encourage an increase in employee performance at the State Polytechnic of Malang. Keywords: Transformational Leadership Style, Work Motivation, Job Satisfaction, Employee Performance.